Repurposing CRISPR-Cas12b for mammalian genome engineering. Issue 1 (December 2018) - Teng, Fei; Cui, Tongtong; Feng, Guihai; Guo, Lu; Xu, Kai; Gao, Qingqin; Li, Tianda; Li, Jing; Zhou, Qi; Li, Wei
Abstract The prokaryotic CRISPR-Cas adaptive immune systems provide valuable resources to develop genome editing tools, such as CRISPR-Cas9 and CRISPR-Cas12a/Cpf1. Recently, CRISPR-Cas12b/C2c1, a distinct type V-B system, has been characterized as a dual-RNA-guided DNA endonuclease system. Though being active in vitro, its cleavage activity at endogenous genome remains to be explored. Furthermore, the optimal cleavage temperature of the reported Cas12b orthologs is higher than 40 °C, which is unsuitable for mammalian applications. Here, we report the identification of a Cas12b system from theAlicyclobacillus acidiphilus (AaCas12b), which maintains optimal nuclease activity over a wide temperature range (31 °C–59 °C). AaCas12b can be repurposed to engineer mammalian genomes for versatile applications, including single and multiplex genome editing, gene activation, and generation of gene mutant mouse models. Moreover, whole-genome sequencing reveals high specificity and minimal off-target effects of AaCas12b-meditated genome editing. Our findings establish CRISPR-Cas12b as a versatile tool for mammalian genome engineering.